Implementation of Betulungan on Multiethnic Women in Preserving The Haul Tradition in Samarinda East Kalimantan - Sunardi; Rusmawaty, Desy; Sultan, Muhammad (Talenta Publisher, 2024)
This ethnographic study investigates the Haul tradition's execution in Samarinda, East Kalimantan, emphasising the procedures and challenges of preserving this significant religious and cultural event. The Haul custom- an Islamic observance that pays tribute to esteemed progenitors or saints, is of great spiritual significance; however, it is currently facing contemporary challenges, such as ethnic diversity and generational shifts. Betulungan, a native term that signifies cooperation and communal assistance, is the foundation of the Haul's prosperity in Samarinda. Betulungan's role in fostering collaboration among women from various ethnic backgrounds—Javanese, Banjar, Kutai, and Dayak—who are involved in the administration and maintenance of the Haul is further clarified in this study. The research employed a case study methodology, utilising data collected from five key informants chosen for their substantial contributions to the organization of the Haul within their communities. The neighborhood leader, a critical participant in organising community events, is identified as a key informant because he fosters collaboration and ensures inclusion in this multiethnic environment. The research, conducted through participant observation and exhaustive interviews, illustrates how Betulungan is a conduit for bridging ethnic divides and promoting interethnic collaboration in preparing food, rituals, and logistics for the Haul. The data indicate that Betulungan fosters a collaborative environment where women, regardless of ethnicity, unify to achieve a common spiritual goal, thereby preserving the Haul heritage and enhancing social cohesiveness. In response to the socio-cultural dynamics of a modernizing, multiethnic Samarinda, the Haul heritage has continued to evolve, with the culture of mutual assistance being crucial to its preservation. The research improves understanding of the substantial role those local cooperative behaviors play in conserving cultural and religious traditions among various groups.